2018
DOI: 10.1159/000494215
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Markers, Genotype, and Inflammation in Pediatric Inflammatory Bowel Disease: A Danish Population-Based Study

Abstract: Background: Our aim was to characterize the biochemical markers at diagnosis in patients with inflammatory bowel disease (IBD), to assess the utility of these to predict disease course and investigate if genotype influences biochemical markers of inflammation. Summary: Patients were included from a population-based pediatric IBD cohort from Eastern Denmark. Data on biochemical markers and medical as well as surgical treatment were registered at diagnosis, 30 days, 6 and 12 months after diagnosis. Fifty-two sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Based on our results, serum IgG and IgA titers may be useful as disease activity markers in the evaluation of pediatric IBD. Besides, our study found a strong correlation between serum albumin levels and quantitative values of IgG and IgA ASCAs, which may indicate that greater quantitative levels re ect more severe illness, similar to earlier studies demonstrating that serum albumin might indicate disease severity [19].…”
Section: Discussionsupporting
confidence: 90%
“…Based on our results, serum IgG and IgA titers may be useful as disease activity markers in the evaluation of pediatric IBD. Besides, our study found a strong correlation between serum albumin levels and quantitative values of IgG and IgA ASCAs, which may indicate that greater quantitative levels re ect more severe illness, similar to earlier studies demonstrating that serum albumin might indicate disease severity [19].…”
Section: Discussionsupporting
confidence: 90%
“…Crohn's patients with higher CRP and lower albumin at diagnosis are expected to have a more aggressive course [12,[47][48][49]. Also, growth failure has fairly consistently been associated with disease severity at diagnosis [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate that greater quantitative levels of serum ASCA titers reflect more severe disease, similar to earlier studies demonstrating that serum albumin might indicate disease severity. 19 In the correlation analysis, when the log value was applied to ASCA IgG and IgA titer and variables, the effect size of CRP and ESR was found to be larger, showing that serum ASCA IgG and IgA titer are more related to inflammatory responses than other variables. Based on our results, serum ASCA IgG and IgA titers may be useful as serological biomarkers in evaluating the disease activity of pediatric IBD.…”
Section: Discussionmentioning
confidence: 95%